2016
DOI: 10.3892/mmr.2016.5334
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone A induces T24 bladder cancer cell apoptosis by increasing intracellular calcium levels

Abstract: Abstract. Licochalcone A (LCA) has been reported to significantly inhibit cell proliferation, increase reactive oxygen species (ROS) levels, and induce apoptosis of T24 human bladder cancer cells via mitochondria and endoplasmic reticulum (ER) stress-triggered signaling pathways. Based on these findings, the present study aimed to investigate the mechanisms by which LCA induces apoptosis of T24 cells. Cultured T24 cells were treated with LCA, and cell viability was measured using the sulforhodamine B assay. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
5
22
0
Order By: Relevance
“…As a universal secondary messenger, Ca 2+ plays a central role in a wide range of cellular processes, including cell apoptosis . The Ca 2+ dependent apoptosis is well defined in numerous reports . In our study, we found that the intracellular Ca 2+ concentration was lower when CD38 over‐expressed compared with control group cells.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As a universal secondary messenger, Ca 2+ plays a central role in a wide range of cellular processes, including cell apoptosis . The Ca 2+ dependent apoptosis is well defined in numerous reports . In our study, we found that the intracellular Ca 2+ concentration was lower when CD38 over‐expressed compared with control group cells.…”
Section: Discussionsupporting
confidence: 55%
“…[35][36][37] The Ca 2+ dependent apoptosis is well defined in numerous reports. [38][39][40] In our study, we found that the intracellular Ca 2+ concentration was lower when CD38 over-expressed compared with control group cells.…”
Section: Discussionsupporting
confidence: 50%
“…Mitochondrial Membrane Potential Measurements : 1 × 10 6 HeLa cells were seeded in a 6‐well plate and cultured overnight. On the next day, the culture medium was replaced by fresh medium containing Ato‐ICG‐GNPs and MMP‐2 enzyme, and the incubation was allowed to proceed for 24 h. The mitochondrial transmembrane potential was determined by staining with JC‐1 probe . In a typical experiment, 1 mL of JC‐1 operating fluid (5×) was added into the medium for a 20 min of staining, followed by the washing with specialized, precooled JC‐1 wash solution (1×).…”
Section: Methodssupporting
confidence: 90%
“…Few studies have examined the association between CALCR gene variations and disease, and the relationship between CALCR gene variations and toxic reaction in response to CRT has not been reported. An elevated intracellular calcium level may induce cell apoptosis [33,34] . We speculate that functional mutation of this SNP may decrease the intracellular concentration of Ca 2+ , thereby leading to cervical lymph node cell survival.…”
Section: Discussionmentioning
confidence: 99%